γ‐Tocopherol‐enriched mixed tocopherol diet inhibits prostate carcinogenesis in TRAMP mice - Barve, Avantika; Khor, Tin Oo; Nair, Sujit; Reuhl, Kenneth; Suh, Nanjoo; Reddy, Bandaru; Newmark, Harold; Kong, Ah‐Ng (International journal of cancer, 2009)
γ‐tocopherol (γ‐T) alone or in combination with α‐tocopherol has been shown to suppress biomarkers of oxidative stress in asthamatics and human subjects with metabolic syndrome. Oxidative stress has been implicated as a key event in prostate carcinogenesis. Hence, the purpose of this study was to examine the effects of γ‐tocopherol‐enriched mixed tocopherol diet on prostate carcinogenesis in a murine prostate cancer model (TRAMP). 8 week old TRAMP males were fed 0.1% γ‐T‐enriched mixed tocopherol diet that contained 20‐fold higher levels of γ‐tocopherol, and roughly 3‐fold higher levels of α‐tocopherol. The effect of such diet on tumor and PIN development was observed. The expression of phase II detoxifying, antioxidant enzymes and Nrf2 mRNA and protein were determined by RT‐PCR, immunohistochemistry and western blotting techniques. Treatment with γ‐T‐enriched mixed tocopherols significantly suppressed the incidence of palpable tumor and Prostate Intraepithelial Neoplasia (PIN) development without affecting the expression of the transgene (SV‐40). Tumor progression occurred with a significant suppression of antioxidant enzymes such as catalase, superoxide dismutase, glutathione peroxidase, heme‐oxygenase‐1 and phase II detoxifying enzymes. Treatment with γ‐T‐enriched mixed tocopherol diet upregulated the expression of most detoxifying and antioxidant enzymes. Nrf2—a redox sensitive transcription factor known to mediate the expression of phase II detoxifying enzymes, was also significantly upregulated following treatment with γ‐T‐enriched mixed tocopherol diet. γ‐T‐enriched mixed tocopherols significantly up‐regulated the expression of Nrf2 and its related detoxifying and antioxidant enzymes thereby suppressing PIN and tumor development. © 2008 Wiley‐Liss, Inc.